The Innovative Power of Partnership - Ashlee Pollard (The University of Alabama, 2022)
Review of the book: Ching Mey See (Editor), Leadership Training in University-community Engagement, 2016, 92 pages. ISBN: 978-967-461-042-5 (Print), e-ISBN: 978-967-461-052-4